Influence of Technology Acceptance and Marketing Mix in Consumer Perspective on Purchase Decision of Chinese Electric Vehicles by Thai Consumers in Bangkok Metropolitan Area - Kumpirarusk, Panuwong; Denyuk, Nattapon; Huang, Ing-wei; Bhundarak, Komn (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2025)
The objective of this research was to study demographic factors, technology acceptance factors, and Marketing Mix in consumer perspective factors affecting purchase decision of Chinese electric vehicles by Thai consumers in Bangkok Metropolitan area. It was quantitative research based on 406 samples, and statistical procedures were carried out to prove scale and data appropriateness. Data received through the online survey during October and November 2022 was analyzed by descriptive statistics, independent t-Test, One-way ANOVA, factor analysis and multiple regression at the significance level of 0.05. The results of the study revealed that different age ranges affected purchase decision differently; three technology acceptance factors including perceived usefulness and ease to use technology, social influence on technology, and technology anxiety affected purchase decision; in terms of marketing mix in consumer perspective, value for consumers affected purchase decision, and these four significant factors could explain 66.4% of the variance in purchase decision of Chinese electric vehicles. The manufacturers of electric vehicles can use the research results to improve product design and development strategies as well as marketing strategies to increase consumer confidence in purchasing and using electric vehicles.